Electric-field-induced disclination migration in a Grandjean-Cano wedge - Stromer, J; Marenduzzo, D; Brown, C; Yeomans, J; Raynes, E (2006)
The behavior of a disclination line in a Grandjean-Cano wedge is investigated under an electric field applied normal to the cell substrates. The focus of attention is the first disclination, separating the untwisted and the π -twisted area. This disclination line shows a field dependent migration process that was observed in the cholesteric mixture ZLI-1132/S811. The dynamics of this migration process is studied experimentally and is compared with two theoretical models. One model utilizes a two-dimensional lattice Boltzmann approach to predict the initial migration movement, whereas a one-dimensional continuum model allows a full analysis of the experimental results. © 2006 American Institute of Physics.